Development of a mouse model for testing therapeutic agents: the anticancer effect of dienogest on endometrial neoplasms. (3rd May 2016) - Saito, Fumitaka; Tashiro, Hironori; Yamaguchi, Munekage; Honda, Ritsuo; Ohba, Takashi; Suzuki, Akira; Katabuchi, Hidetaka
Abstract: Objective : As the number of younger women with endometrial carcinoma has increased, fertility-sparing treatments have received more attention. Although there have been several reports on conservative treatments with progestins for endometrial carcinoma, only medroxyprogesterone acetate (MPA) is available in Japan. Dienogest has been developed as a fourth-generation progestin for treating endometriosis. Because of its high progesterone activity, its antitumor activity has attracted attention. In this study, we investigated the anticancer effect of dienogest on endometrial neoplasms using mouse model of endometrial carcinoma. Methods/materials : Pten loxP/loxP mice were injected with MPA or dienogest subcutaneously to evaluate the anticancer effect against endometrial neoplasms that developed in the mice. One week after injections, histopathological analyzes were performed. Results : Endometrial neoplasms were found in one of the eight (12.5%) mice from each group treated with either dienogest or MPA. In contrast, they were found in seven of eight (87.5%) mice not treated with progestins. Each progestin treatment showed anticancer activity against endometrial neoplasms that developed in the mice compared to those without treatment. Conclusions : Dienogest and MPA showed potent anticancer activity against endometrial neoplasms in our mouse model. The present study demonstrated that dienogest might be a useful therapeutic agent for human endometrial neoplasms.